Design of control systems for regulation of mean arterial blood pressure of hypertension patients - Zheng, Hang (2008)
It is known that postoperative hypertension is common in cardiac patients and untreated hypertension patients may result in complications. This thesis mainly presents a fuzzy logic multiple-model adaptive control system for postoperative blood pressure management. Multiple-model adaptive control (MMAC) algorithm is used to identify the patient model, and it is a feasible system identification method even in the presence of large noise. A fuzzy control (FC) method is used to design a controller bank.